Study of the morphological and anatomical structure and establishment of diagnostic signs of the aboveground part of the Sakhalin (giant) knotweed (Reynoutria sachalinensis (F. Schmidt) Nakai) - Alrikabi, Abdulrazzaq Yasir Hussain; Protska, Viktoriia; Zhuravel, Iryna (Annals of Mechnikov's Institute, 2021)
Introduction. Reynoutria sachalinensis (F. Schmidt) Nakai belongs to the plant family Polygonaceae Juss., which is native to the Far East. Reynoutria sachalinensis (F. Schmidt) Nakai is grown in Ukraine, as an ornamental, fodder and honey plant. It is also considered an invasive plant. According to the literature, the aerial part of the Reynoutria sachalinensis (F. Schmidt) Nakai accumulates flavonoids, stilbenes, anthracene derivatives, coumarins, hydroxycinnamic and amino acids, minerals elements, vitamins, alkaloids, essential oil, phytoestrogens and tannins. In traditional medicine of Asia Reynoutria sachalinensis (F. Schmidt) Nakai is used to treatment burns, gallstones, hepatitis and osteomyelitis, carbuncles, toothache, arthralgia, amenorrhea, jaundice, cough, hemorrhoids, heartburn, tumors, hypertension, bleeding. The rich chemical composition and wide use in traditional medicine indicate the prospects for the development of drugs based on Reynoutria sachalinensis (F. Schmidt) Nakai. However, for its full application in medicine, a necessary condition is the availability development of draft monograph for medicinal herbal drugs of Reynoutria sachalinensis (F. Schmidt) Nakai, prescribed by the SPhU. The format of monographs on medicinal herbal drugs provides for the establishment of criteria for identification of medicinal herbal drugs, including specific macro- (Identification A) and microscopic (Identification B) diagnostic features. Materials and methods. Using of conventional methods of light microscopy, the morphological and anatomical structure of the aboveground part of Reynoutria sachalinensis (F. Schmidt) Nakai. was studied and its main macro- and microscopic diagnostic features were established. Results and discussion. The main macroscopic diagnostic features of the aboveground part of the Reynoutria sachalinensis (F. Schmidt) Nakai. (Identification A) include the presence of pubescence on leaf blades; extrafloral nectaries at the base of petioles in the form of brown spots and notches. The plant is characterized by hollow stems with tubular, membranous, brown bells in the internodes. The main microscopic diagnostic features of the herbal drugs of the Reynoutria sachalinensis (F. Schmidt) Nakai. (Identification B) were hypostomatic type of leaf blade. Anomocytic type of respiratory system is characteristic of leaves of the Reynoutria sachalinensis (F. Schmidt) Nakai. On the epidermis of both sides of the leaf blade there are simple, cone-shaped hairs covered with a thick layer of cuticle, and glands with a unicellular stalk, 4-8-cell head and orange secretion. Along the margin of the leaf blade there are papillary outgrowths of the epidermis. The conductive system of the central vein of the leaf, petioles and stems of the Reynoutria sachalinensis (F. Schmidt) Nakai. is formed by one large adaxial and 7-10 small abaxial collateral open bundles, which are located concentrically in a circle. They are all surrounded by a single-row coating, which is formed by large cells with yellow pigment. The ventral conducting bundle also has a sclerenchymal coat. The pubescence of the petioles is represented by simple unicellular hairs. On the epidermis of the petioles there are stomata of the anomocytic type. At the base of the petioles of leaves of the Reynoutria sachalinensis (F. Schmidt) Nakai there are extrafloral nectaries with brown secretion. The stem has a multifaceted shape in cross section. The anatomical structure of the stem is also characterized by the presence of lignified sclerenchyma, which is located concentrically and interrupted by medullary rays. The core parenchyma is formed by large isodiametric cells, which in the central part collapses and forms a cavity. The bells of the Reynoutria sachalinensis (F. Schmidt) Nakai. are formed by two incompletely fused brown stipules. Anomocytic stomata are rare. Along their margin there are papillary outgrowths of the epidermis, and at the base the epidermis has a folded. Stomata of the anomocytic type and simple single-celled hairs are rarely found on the outer and inner epidermis of the petals of flowers. Along the margin of the petal, the inner epidermis has papillar. Druse of calcium oxalate are found in the mesophyll of leaves, petioles, stems and flowers of Reynoutria sachalinensis (F. Schmidt) Nakai. Small, spherical pollen grains with a thin, dense, smooth exine and a reduced ovary are also characteristic diagnostic features of the generative organs of the Reynoutria sachalinensis (F. Schmidt) Nakai. Conclusions. The obtained results do not contradict the information found in the literature, however, indicate some non-fundamental differences in the morphological and anatomical structure of some aboveground organs of the Reynoutria sachalinensis (F. Schmidt) Nakai depending on the climatic conditions of plant place growth. The experimental data will be used in the development of development of draft monograph for medicinal herbal drugs of the Reynoutria sachalinensis (F. Schmidt) Nakai. Key words: Sakhalin (giant) knotweed, Reynoutria sachalinensis (F. Schmidt) Nakai), anatomy, morphology. DOI: 10.5281/zenodo.5761273